Performance and behavior analysis of piezoelectric energy harvesting floor tiles - Panthongsy, Phosy; Isarakorn, Don; Hamamoto, Kazuhiko; Janphuang, Pattanaphong (My University, 2019)
This paper presents the performance and behavior analysis of two unlike piezoelectric energy harvesting floor tiles in which they are functioned with different frequency up-conversion strategies to achieve the high energy conversion efficiency from low and variable-frequency vibration as the human footstep. One of such strategies is to convert the frequency of piezoelectric bimorph up through the magnetic interaction between a permanent magnet and an iron plate, while another one is achieved on that through the mechanical impact between a cover plate and a wall of the floor tile. Experimentally, the floor tiles having one piezoelectric bimorph inside of them are prototyped and then mounted to their individual input-exciting kit to investigate the energy harvesting performance. The input-exciting kits are employed to simulate the human footstep on floor tiles. The results show that the floor tile with frequency up-converting mechanism based on mechanical impact should be a better option for energy harvesting from human footstep due to the low-profile structure and good energy harvesting performance. Moreover, its operational way can result in long-lasting piezoelectric bimorph. When a cover plate is actuated to move down with the velocity of 54.13 mm/s and then released, the floor tile can produce the average power of 0.82 mW at load resistance approximately of 55.68 kΩ.
Keywords: energy harvesting floor tiles; frequency up-conversion techniques; low-frequency vibration energy harvesting; Piezoelectric energy harvester